Strategic Decision-Making in The Era of Artificial Intelligence:A Multi-Dimensional Evaluation of ‎Opportunities, Challenges and Ethical Concerns - Kumar , Neeraj; Yadav , Swati; Charitha, Bondili Naga Sai Bhavya; Retd, Dr. Chacko Jose P.; Khound, Dr. Kaveri; Khandhadiya, Ravi Vijaybhai; Rupani, Dr. Jigar; Yadav , Nikita (International Journal of Accounting and Economics Studies, 2025)
This paper explores the impacts of Artificial Intelligence (AI) on strategic business decisions, focusing on the opportunities, hurdles ‎, and ethical aspects associated with embedded AI in organizations. With a mixed-methodology, the study does not rely solely upon ‎quantitative data to assess decision-making consequences influenced by AI and machine technologies, but includes qualitative ‎feedback from business leaders on the ground. The findings imply that while AI significantly enhances data analysis and informs ‎strategic decisions, it also raises issues about transparency, accountability, and whether there may be bias embedded in decisions ‎driven by algorithms. Nowhere is this more apparent than in the healthcare sector, the implications of which are significant as ‎greater reliance on AI can facilitate improving operational efficiencies and patient results, but it also demands robust ‎frameworks to confront the ethical issues around patient privacy and informed consent. Ultimately, this work fuels the debate ‎regarding the transformative effect of AI on business strategy and highlights that the incorporation of ethical considerations cannot ‎be compromised if we are to develop guidelines in this area. These recommendations can help to mitigate AI-related risks and ‎enable responsible AI adoption in the healthcare and other contexts, and pave the way for future research on the emergent ‎technology-strategic management connection‎.
Keywords: Artificial Intelligence (AI); Strategic Business Decisions; Ethical Considerations; Healthcare; Decision-Making Outcomes